2020
DOI: 10.1002/cam4.2852
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter phase II trial of paclitaxel, carboplatin, and cetuximab followed by chemoradiotherapy in patients with unresectable locally advanced squamous cell carcinoma of the head and neck

Abstract: Background Induction chemotherapy (IC) in locally advanced squamous cell carcinoma of the head and neck (LA‐SCCHN) often compromises compliance with subsequent chemoradiotherapy (CRT), which negatively affects outcomes. Here, we assessed the combination of paclitaxel (PTX), carboplatin (CBDCA), and cetuximab (Cmab) as IC for unresectable LA‐SCCHN. Methods Induction chemotherapy consisted of weekly CBDCA area under the plasma concentration‐time curve = 1.5, PTX 80 mg/m2 and Cmab with an initial dose of 400 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Thirty-one patients were elderly or frail (EF). The most common reasons patients did not receive cisplatin were performance status (13 patients), hearing loss (11), concern for nephrotoxicity (6) and age (5).…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-one patients were elderly or frail (EF). The most common reasons patients did not receive cisplatin were performance status (13 patients), hearing loss (11), concern for nephrotoxicity (6) and age (5).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…9 Several studies have showed this regimen yields promising results when used as an induction chemotherapy for locally advanced disease, with response rates ranging from 70% to 97%. 5,[10][11][12][13] PCC has also been studied for patients with metastatic or recurrent incurable disease, and has shown promising response with tolerable toxicity rates. 14 Although it is thought that this treatment combination is less toxic than some of the other standard-of-care systemic therapies, and it is often used as induction therapy prior to radiation or surgery in more frail patients as well as in patients with recurrent or metastatic disease, there is a relative dearth of evidence supporting its use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck squamous cell carcinoma (HNSCC) accounts for 90% of head and neck cancers [5]. Approximately, 70% of patients with primary HNSCC present with locally or regionally advanced disease (stage III or IV) [6], which recurs in approximately 40-65% of cases after primary therapy with surgery and radiation, with or without chemotherapy [6][7][8][9][10]. Patients with locally advanced HNSCC have a very poor prognosis, with a 5 year survival rate of only 10-50%, depending on the stage and location of the lesion [6].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody-dependent cellular cytotoxicity, the main mechanism of anticancer action of cetuximab, can be further increased by paclitaxel [ 148 ]. Co-administration of cetuximab and paclitaxel was reported to be effective not only for the treatment of head and neck carcinoma but also for cervical, esophageal, urothelial, or non-small cell lung carcinoma, on which there are currently active clinical trials [ 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 ]. Another recently reported promising combination of paclitaxel with immunotherapy involves pamrevlumab (FG-3019; FibroGen, Inc., San Francisco, USA).…”
Section: Introductionmentioning
confidence: 99%